7(x-2)+2x=3(x-8)+x-5

Simple and best practice solution for 7(x-2)+2x=3(x-8)+x-5 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7(x-2)+2x=3(x-8)+x-5 equation:



7(x-2)+2x=3(x-8)+x-5
We move all terms to the left:
7(x-2)+2x-(3(x-8)+x-5)=0
We add all the numbers together, and all the variables
2x+7(x-2)-(3(x-8)+x-5)=0
We multiply parentheses
2x+7x-(3(x-8)+x-5)-14=0
We calculate terms in parentheses: -(3(x-8)+x-5), so:
3(x-8)+x-5
We add all the numbers together, and all the variables
x+3(x-8)-5
We multiply parentheses
x+3x-24-5
We add all the numbers together, and all the variables
4x-29
Back to the equation:
-(4x-29)
We add all the numbers together, and all the variables
9x-(4x-29)-14=0
We get rid of parentheses
9x-4x+29-14=0
We add all the numbers together, and all the variables
5x+15=0
We move all terms containing x to the left, all other terms to the right
5x=-15
x=-15/5
x=-3

See similar equations:

| 12x-7=5x+133 | | 4x+7+6x=12+5x-25 | | X(2x-1)^2-x(2x-1)(2x+1)=0 | | 3/2x-5=7/3 | | 2x+3x+8=6x+5 | | -8x=+16 | | 8n-9=15 | | 1/x=3/2+x | | 6n+18=3(3n–2) | | 1/3x²-5/3x+2=0 | | 8x+6=15x-15 | | x+13=-3+1 | | 3x-1=5x+3-1 | | (x+16)+(8x-7)=180 | | (x+16)+(8x+7)=180 | | 4x+24=5x+44 | | -4-3y=8 | | x+16+8x+7=180 | | 3(x-5)=2(3×-1)-19 | | 3(3)-4y=13 | | 5x+6-9x=9 | | 8x-2x6x=52 | | 1.25+0.2=-1.667x+0.75 | | (3a)=² | | 2(x+5)=83 | | 5x+25=7x-23 | | 82-h-29=18 | | (x-12)(2x+25)=0 | | 3p+2p-p=# | | 1/4x^2=61/4 | | 3x²+21x=0 | | (e+1)×2=12 |

Equations solver categories